2016
DOI: 10.1021/acs.inorgchem.6b01634
|View full text |Cite
|
Sign up to set email alerts
|

In-Depth Magnetic Characterization of a [2 × 2] Mn(III) Square Grid Using SQUID Magnetometry, Inelastic Neutron Scattering, and High-Field Electron Paramagnetic Resonance Spectroscopy

Abstract: A tetranuclear [2 × 2] grid-like manganese(III) Schiff base complex, Mn, has been synthesized and characterized by single-crystal X-ray crystallography. Direct-current magnetization measurements were performed on the system and proved to be insufficient for an accurate magnetic model to be deduced. Combined inelastic neutron scattering (INS) and electron paramagnetic resonance (EPR) experiments provided the necessary information in order to successfully model the magnetic properties of Mn. The resulting model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The ground state of the Mn­(III) ion is the even-spin S = 2 state, and complexes containing Mn­(III) exhibit typically large zero-field splitting with the D parameter of the spin Hamiltonian (1) of a few cm –1 , making them very difficult to investigate by standard EPR, as the small microwave quantum energy cannot cause transitions between the M S levels Interestingly, there is one exception to this: the M S = 2 and M S = −2 levels of the S = 2 state are split very little in the absence of the magnetic field (approximately 3 E 2 / D ), and a nominally “forbidden” Δ M S = 4 transition sometimes appears in X-band EPR at an effective g value of ∼8. , The transition under question is however only weakly sensitive to the D parameter. HFEPR offers an effective remedy to these problems. The microwave quantum energies available to us are up to ∼20 cm –1 (∼600 GHz) and allow observation of all possible transitions in Mn­(III) systems. Complexes of Mn­(III) tend to produce HFEPR spectra of good quality.…”
Section: Resultsmentioning
confidence: 99%
“…The ground state of the Mn­(III) ion is the even-spin S = 2 state, and complexes containing Mn­(III) exhibit typically large zero-field splitting with the D parameter of the spin Hamiltonian (1) of a few cm –1 , making them very difficult to investigate by standard EPR, as the small microwave quantum energy cannot cause transitions between the M S levels Interestingly, there is one exception to this: the M S = 2 and M S = −2 levels of the S = 2 state are split very little in the absence of the magnetic field (approximately 3 E 2 / D ), and a nominally “forbidden” Δ M S = 4 transition sometimes appears in X-band EPR at an effective g value of ∼8. , The transition under question is however only weakly sensitive to the D parameter. HFEPR offers an effective remedy to these problems. The microwave quantum energies available to us are up to ∼20 cm –1 (∼600 GHz) and allow observation of all possible transitions in Mn­(III) systems. Complexes of Mn­(III) tend to produce HFEPR spectra of good quality.…”
Section: Resultsmentioning
confidence: 99%
“…Previously reported dimanganese(III,IV) and dimanganese(II,III) systems have been investigated by HFEPR, [35][36][37] and more importantly, so have dimanganese(III) complexes, such as a μ-oxido complex by Retegan et al, 10 a μ-fluorido complex by Pedersen et al, 8 and a system more relevant to those reported here, namely a dimanganese(III,III) complex without any bridging atoms, but with covalent connections between the two Mn III ions via two trans four-bond π-conjugated O-C-C-C-O pathways. 28 A tetranuclear complex comprising a square grid of Mn III ions linked by Schiff base ligands has also been studied by HFEPR, 38 but this complicated spin system is beyond the present study.…”
Section: Introductionmentioning
confidence: 99%
“…With traditional spectrometers, one would have to undertake three measurement runs, taking approximately three times longer. This approach obviously has great potential, and the present study represents one of the first efforts to exploit it for a molecular magnetic compound [40,41]. Within this comprehensive work, we have been able to extract a meaningful physical picture for the magnetic ground state of the parent compound Tb 2 (µ-N 2 2− ).…”
Section: Introductionmentioning
confidence: 85%